PENGARUH PEMBERIAN EKSTRAK DAUN STEVIA DALAM MENJAGA KESTABILAN KADAR GULA DARAH PENDERITA DIABETES: THE EFFECT OF ADMINISTRATION OF STEVIA LEAF EXTRACT IN MAINTAINING STABLE BLOOD SUGAR LEVELS IN DIABETES PATIENTS - Nurrahman, Annisa Indah; Permadi, Andri Nur; Safanah, Ashila Nur; Puspita, Dini Aulia; Anugrah, Rikman; Putra, Subhan Manggala; Ridwan, Heri; Setiadi, Diding Kelana (Intan Husada : Jurnal Ilmiah Keperawatan, 2024)
Background. Diabetes Mellitus is an example of a type of disease that is not contagious and attracts a lot of attention. DM sufferers are required to control blood sugar levels by maintaining dietary rules so that blood sugar levels remain controlled. Blood sugar levels will increase drastically after eating foods that contain carbohydrates or sugar in them.Stevia is a natural sweetener substitute for sugar that comes from the stevia plant. Stevia leaves are hypoglycemic which functions to lower blood glucose levels for people with diabetes mellitus. Purpose. This study aims to determine the effect of stevia sugar on the stability of blood sugar in diabetes sufferers. Methods. The method used is a systematic literature review. Data collection is carried out by recording all articles that have similar research in the research report. The articles used in this search are national and international journals taken from Google Scholar, Crossref, Semantic Scholar and Scopus databases in 2019-2023 using the Publish or Perish application. Result. Based on the results of the literature review, it was found that stevia has an effect on reducing blood glucose levels in DM sufferers. Consumption of stevia leaf extract plays an important role in reducing levels of glucose, cholesterol, total fat and other blood characteristics. Conclusion. Based on the results of research that has been carried out, it can be concluded that stevia leaf water extract can maintain and even reduce blood glucose levels in diabetes patients because serum insulin and adiponectin levels increase dramatically.